Pengaruh Penerapan Model Project Based Learning terhadap Hasil Belajar Tematik Terpadu di Sekolah Dasar - Kurnia Nur’afita Sari; Yanti Fitria (Universitas Negeri Padang, 2020)
The study in the background oflearners not yet involved in the work of the project to promote learning, learners are not active in learning groups and solving problems, creating the work/product to some students have low learning result. The study was intended to describe the impact of the project based learning model on learning toward the results of learning in integrated thematic learning at country fifth grade elementary school cluster 2 Lubuk Kilangan City of Padang. The kind of research is a quantitative in the form quasy experiment design with the non-equivalent control group design. Cluster random sampling technique. The subject of research is a fifth grade elementary school 01 Bandar Buat. Research shows: the average pretest of experimwntal classes that apply learning using the model project based learning is 50,42 and the average study posttest for experimental class testing is 85,76. Whereas the average control class results from learning pretest are 64,4 and the average result of learning after being aynthesized using a conventional approach has a 69,19 posttest average. Based on the results of the hypothesis test done with test t, obtained t’cunt= 6,42>ttable = 2,0096. Thus, project based learning has a significant impact on learning integrated thematic learning at country fifth grade elementary school 01 Bandar Buat.